Invalidade das deliberações de fundos de investimento - Miranda, Pedro Luiz de (2023)
This study aims at analyzing the invalidity of investment funds’ resolutions, one of the main characters responsible for conveying wealth, considering the principles of Private Law, the recent modifications in the Brazilian Civil Code and the rules issued by the Brazilian Securities Exchange Commission. Pursuant to the current Brazilian law system, investment funds are deemed as a pooling of funds, organized as a condominium sui generis, which shall invest its resources in financial assets, good and rights of any kind. In order to comprehend such a concept, it is mandatory to identify the legal nature of investment fund and its functioning, which is enabled by acts of services renders and by the declaration of will of the condominium members. Upon understanding these aspects, it will be analyzed the scenarios in which investment funds’ resolutions are invalid and the effects inflicted on third parties by such an invalidity. By the end, it is expected that the conclusions reached in this study help to contribute with the stability of juridical relationships arose from the conveyance of wealth and, hence, provide safety to commercial negotiations